Injury mechanisms and electromyographic changes after injury of the recurrent laryngeal nerve: Experiments in a porcine model. Issue 2 (30th September 2017) - Brauckhoff, Katrin; Svendsen, Øyvind S.; Stangeland, Lodve; Biermann, Martin; Aas, Turid; Husby, Paul J. A.
Abstract: Background: Recurrent laryngeal nerve (RLN) injury during surgery may reveal differences in electromyographic (EMG) changes after sustained compression or traction. Methods: In 20 pigs with the NIM‐FLEX EMG‐endotracheal tube, EMG was recorded at baseline, during sustained RLN compression, or traction until 70% amplitude decrease and during 30 minutes of recovery. Results: Seventy percent amplitude decrease from baseline was reached after 110 ± 98 seconds (compression group) and 2034 ± 2108 seconds (traction group). Traction induced a pronounced latency increase, peaking at 122 ± 8% in contrast to compression with 106 ± 5% ( P < .001). The EMG amplitude recovery to ≥50% of baseline failed in 7 nerves after compression and 8 nerves after traction. Conclusion: Compression caused a fast decrease of EMG amplitude with minor effects on latency. In contrast, RLN traction showed early and significant latency increase preceding a delayed amplitude decrease. Recovery rate of the EMG signals were similar in both groups.